2009
DOI: 10.1152/ajpcell.00442.2008
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell differentiation into smooth muscle cells is mediated by Nox4-produced H2O2

Abstract: NADPH oxidase (Nox4) produces reactive oxygen species (ROS) that are important for vascular smooth muscle cell (SMC) behavior, but the potential impact of Nox4 in stem cell differentiation is unknown. When mouse embryonic stem (ES) cells were plated on collagen IV-coated dishes/flasks, a panel of SMC-specific genes was significantly and consistently upregulated. Nox4 expression was markedly correlated with such a gene induction as confirmed by real-time PCR, immunofluorescence, and Western blot analysis. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
173
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(185 citation statements)
references
References 43 publications
10
173
2
Order By: Relevance
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The present results suggest that Apocynin and 5-HD act by stimulating differentiation of mesencephalic precursors toward the DA phenotype. The results are consistent with those of previous studies, which have suggested that the redox state modulates differentiation of mesencephalic precursors (Studer et al, 2000;Rodriguez-Pallares et al, 2001Tsatmali et al, 2005), and with those of studies that have suggested that ROS levels affect the phenotype of cells in culture (Li et al, 2006;Xiao et al, 2009), including neurons (Tsatmali et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…On SMCs, TGF-β1 suppresses proliferation while induces differentiation. 14,15 TGF-β2 plays an essential role in the valve formation during embryonic development via endothelial-mesenchymal transition. 16 TGF-β3 negatively regulates TGF-β1-mediated extracellular matrix deposition.…”
mentioning
confidence: 99%
“…Expectedly, data summarised in Supplementary Table S2 showed that a panel of SMC-specific genes (highlighted in yellow) were upregulated by miR-34a overexpression. Importantly, several SMCspecific transcription factors, including serum response factor (SRF), myocardin (Myocd) and myocyte enhancer factor 2C (MEF2c), that were reported to be activated in our SMC differentiation system 11,17 were also significantly upregulated by miR-34a, alongside SirT1 (Supplementary Table S2). Furthermore, overexpression of miR-34a upregulated SRF, myocardin and MEF2c, whereas knockdown of miR-34a downregulated these genes (Supplementary Figure S2), suggesting that miR-34a works in concert with these SMC transcription factors during SMC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed protocols for mouse ESCs (mESCs) (ES-D3 cell line, CRL-1934; ATCC, Manassas, VA, USA) culture and SMC differentiation were described in our previous studies. [11][12][13][14]17,22,34,43,44 The Shef-1, 2, 3, 6, and 7 human ESC lines were obtained from the United Kingdom Stem Cell Bank (UKSCB, Hertfordshire, UK) and maintained in our Laboratory as described in our previous study. 18 Briefly, undifferentiated ESCs were dissociated into single cells and seeded onto collagen I/IV (5 Îźg/ml)-coated flasks or plates in differentiation medium (DM, MEM alpha medium (Gibco, Carlsbad, CA, USA) supplemented with 10% FBS, 0.05 mM 2-mercaptoethanol, 100 U/ml penicillin, and 100 Îźg/ml streptomycin) for 0-9 days prior to further treatment.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%